1.
a) Można od razu podstawić pod niewiadome
[2*0.5*(-1)²]⁶ / [-2*0,5*(-1)]² = [1*1]⁶ / [-1*(-1)]² = 1 / [1]² = 1
b) lub uprościć
[tex]\frac{(\frac{1}{2}a^{3}*b^{2})^{4} }{(\frac{1}{6}a^{2}b)^{3}} = \frac{(\frac{1}{16}a^{12}*b^{8}) }{(\frac{1}{216}a^{6}b^{3} )} = \frac{ \frac{1}{16} a^{6}b^{5} }{\frac{1}{216} } =\frac{{ \frac{}{} a^{6}b^{5} }}{16} * \frac{216}{1} = \frac{27a^{6}b^{5} }{2}[/tex]
Podstawiamy i otrzymujemy:
[tex]\frac{27(-\frac{1}{2})^{6}(-\frac{2}{3})^{5} }{2} = \frac{27*\frac{1}{64}*(-\frac{32}{243}) }{2} = \frac{\frac{27*1*-32}{64*243} }{2} = \frac{\frac{-1}{18} }{2} =-\frac{1}{36}[/tex]
c)
[tex]-\frac{3x^{4}y^{6} *8x^{3}y^{6} }{x^{4} y^{4} } = -72x^{3} y^{8}[/tex]
podstawiamy i otrzymujemy
[tex]-72 * (-2,5)^{3} *0,4^{8} = \frac{2304}{3125}[/tex]
2.
[tex]\frac{1}{(1\frac{2}{3})^{2} } - (2,5 * 0,4)^{4} = \frac{9}{25} -1^{4} =-\frac{16}{25}[/tex]